A Case Report of Taenia saginata Infection and Literature Review - Liu L; Ji Y; Feng L; Wang T; Li X; Yang J (Infection and Drug Resistance, 2025)
Luyao Liu,1,2,* Yuanhao Ji,1,* Lanlan Feng,1 Tao Wang,1 Xiaoning Li,2 Jinsun Yang1 1Department of Infectious Diseases, The First Affiliated Hospital of Wannan Medical College, Wuhu, Anhui, 241001, People’s Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital of Wannan Medical College, Wuhu, Anhui, 241001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinsun Yang, Email yangjinsun999999@163.comBackground: Despite the decreasing prevalence of parasitic infections, Taenia saginata infection remains a clinical concern in endemic regions. Humans acquire this infection by consuming raw or undercooked beef containing cysticerci. This study presents a case of T. saginata infection, reviews relevant literature, and underscores the importance of clinical awareness.Case Presentation: We report the case of a 24-year-old female with diarrhea and white nodules in stool, with a history of travel to a T. saginata-endemic region. The patient was successfully treated with traditional Chinese deworming therapy comprising pumpkin seeds and betel nuts, resulting in complete symptom resolution. Diagnosis was confirmed by morphological examination of expelled tapeworms, histological staining of proglottids, and molecular analysis.Literature Review: A PubMed search for “Taenia saginata” identified 92 articles, of which 8 with comprehensive clinical data were included. Eleven cases, including the present one, were analyzed for clinical presentation, treatment, and outcomes. Among the 11 patients, 10 had a history of consuming raw or undercooked beef. Primary symptoms included diarrhea, abdominal pain, and vomiting. When T. saginata affected the biliary system or duodenal papilla, patients had elevated ALT, AST, ALP, and TBL levels, with severe complications like gallbladder perforation requiring surgery. Treatment options included praziquantel, clonidine, albendazole, and traditional Chinese medicine, showing favorable efficacy. Surgery was required in severe cases with positive outcomes.Conclusion: This study suggests T. saginata infection should be considered in differential diagnosis of patients with diarrhea and relevant travel history. When parasitizing the intestinal or biliary tract, it can induce corresponding symptoms. The patient responded well to appropriate medical treatment, including traditional Chinese medicine, with favorable outcomes. Surgical intervention was performed when necessary.Keywords: Taenia saginata, case report, cox1, Chinese medicine, pumpkin seed and betel nut, literature review